Distinct Habits Of Sun Exposures Lead To Different Impacts On Some Facial Signs Of Chinese Men Of Different Ages - Flament F; Amar D; Forichon M; Caron J; Negre C (Dove Medical Press, 2019)
Frederic Flament,1 David Amar,2 Matthieu Forichon,3 Johanna Caron,4 Caroline Negre4 1L’Oréal Research and Innovation, Clichy, France; 2L’Oréal Research and Innovation, Shanghai, People’s Republic of China; 3Nous Avions Rendez-Vous, Lyon, France; 4L’Oréal, Levallois-Perret, FranceCorrespondence: Frederic FlamentL’Oréal Research and Innovation, 9 Rue Pierre Dreyfus, Clichy 92110, FranceTel +33149795334Fax +33149795142Email frederic.flament@rd.loreal.comObjective: To clinically evaluate the impacts of sun exposures on some facial signs of differently aged Chinese men with a distinct behavior vis à vis sun exposures.Methods: Two comparable cohorts of Chinese men (aged 18–75 years old), living in two cities (Shanghai, Hong Kong) were created according to their usual behavior towards sun exposure and through their variable use(s) of a photo-protective product, i.e. non-sun-phobic (N = 127) and sun-phobic (N = 134). Standard photographs (full-face and 45° lateral) allowed to focus on 13 facial signs that were further graded by 15 experts and dermatologists, using a referential Skin Aging Atlas. Absolute differences in the scores of each sign were used (non-sun-phobic minus sun-phobic), by age-classes, to better ascertain the impact of sun exposures and a photo-protecting product, when used.Results: Most facial signs, particularly wrinkles and skin texture, differentiated the two cohorts. Some others showed some erratic changes with age, albeit more pronounced at older ages. In contrast with previous results obtained in Chinese women, the changes observed in men were not only of a lessened severity but were undetected at early ages (<30 years old). Overall, these different behaviors with regard to sun exposures led to significant differences in the facial signs of Chinese men. The latter can be illustrated by two virtual morphings that combine the impacts of both intrinsic and extrinsic aging processes.Conclusion: The present work illustrates, for the first time, some specificities of the impacts of sun exposures on the facial skin of Chinese men, more expressed at older ages, inversely to those observed in Chinese women, occurring at younger ages.Keywords: facial aging, Asian men, solar exposures, photo-aging, skin aging atlas